PENGGUNAAN MODEL PEMBELAJARAN PROBLEMBASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR PAI SISWA KELAS V SD NEGERI 1 TANJUNG BULAN - Ismah Ismah (JOURNAL OF COMMUNITY DEDICATION, 2025)
This research is motivated by the situation of grade V students of SD N 1 Tanjung Bulan in the PAI subject known from the low daily test scores in the first semester of the 2023/2024 school year. The average grade of the class is below KKM 70. The purpose of this study is to determine the improvement of student learning outcomes by using the Problem Based Learning learning model. This research uses a qualitative methodology with a Classroom Action Research (PTK) design whose implementation is carried out during the second cycle. The subject of the study is a student of grade V of SD N 1 Tanjung Bulan with a total of 10 students. The application of the Problem Based Learning model can improve student learning outcomes in PAI subjects. In the first cycle, students have experienced an increase in learning outcomes by 30% and in the second cycle, they have experienced an increase in learning outcomes by 40%. Based on the presentation, it shows that the Problem Based Learning model can improve learning outcomes in PAI subjects in grade V of SD N 1 Tanjung Bulan. This is shown by the completeness of student  learning  from  the  pre-cycle  to  the  second  cycle  which  is  increasing.